2013
DOI: 10.1371/journal.pone.0073484
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Cancer Mutations in Japanese Lung Adenocarcinoma without Sequencing of Normal Tissue Counterparts

Abstract: We analyzed whole-exome sequencing data from 97 Japanese lung adenocarcinoma patients and identified several putative cancer-related genes and pathways. Particularly, we observed that cancer-related mutation patterns were significantly different between different ethnic groups. As previously reported, mutations in the EGFR gene were characteristic to Japanese, while those in the KRAS gene were more frequent in Caucasians. Furthermore, during the course of this analysis, we found that cancer-specific somatic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…This is a very common issue encountered in clinical contexts; therefore, we filtered out possible germline mutations using the databases of the 1000 Genomes Project and 5000 Exomes Project to identify SMs in the absence of matched normal controls. Recently, studies using similar approaches have been reported . We expect that with increasing numbers of normal samples deposited in common databases, these methods can be further refined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is a very common issue encountered in clinical contexts; therefore, we filtered out possible germline mutations using the databases of the 1000 Genomes Project and 5000 Exomes Project to identify SMs in the absence of matched normal controls. Recently, studies using similar approaches have been reported . We expect that with increasing numbers of normal samples deposited in common databases, these methods can be further refined.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, studies using similar approaches have been reported. (8,13) We expect that with increasing numbers of normal samples deposited in common databases, these methods can be further refined. Furthermore, the availability of these databases and methods allows future studies to decrease the cost of germline sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…According to these reports, the prevalence of genetic alterations is 80% to 89% in TP53 and 39% to 67% in RB1 (10-12, 33). Suzuki and colleagues (34) reported that the mutation frequency of TP53 and RB1 in 97 Japanese patients with adenocarcinoma was only 23% and 1%, respectively. In contrast, the mutation frequency of RB1 (26%) in LCNEC in this study was high and similar to that revealed in a previous whole-exome sequencing study of 15 LCNECs (30%; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited estimated precision and recall rates of CLCL detection using short read data at 21 % and 72 %, respectively, for all the cell lines and clinical samples taken together, we applied the constructed analytical pipeline to the whole-exome sequencing data of 514 TCGA lung adenocarcinoma (TCGA-LUAD) 3 and 97 Japanese lung adenocarcinoma (Japanese LUAD) 5 samples. We expected that the detection rate would be inherently lower, reflecting the fact that they are exome sequencing datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Current information on the cancer mutations has been mostly obtained by short read sequencing. Short read sequencing data, generally consisting of tens of millions reads of up to 200-300 bases in length 12 , are the most powerful in detecting point mutations such as single nucleotide variants (SNVs) and short indels 5,13 . Significant efforts have been made to enable the identification of fusion genes by short read sequences 14 .…”
Section: Introductionmentioning
confidence: 99%